Microsoft PowerPoint 2000 : quick tutorial - Murphy, Patricia (Cincinnati, Ohio : South-Western Educational, 2000)
This book is about: Getting started with PowerPoint; Creating a Presentation; Text Editing and Formatting; Working with graphic objects; Inserting tables and charts; Additional PowerPoint features; and Delivering the presentation.
Keywords: Microsoft; PowerPoint; Computer graphics; Microsoft PowerPoint (Computer file); Computer graphics; Business presentations -- Graphic methods -- Computer programs